35 Fetuin-A and toll-like receptor 4 regulate vascular function: role of Nox1. (17th November 2015) - Neves, KB; Lopes, RAM; Leckerman, S; Strembitska, A; Jenkins, C; Thomson, J; Graham, D; Touyz, RM; Montezano, AC
Abstract : FetuinA is associated with endothelial dysfunction, which is regulated by oxidative stress. We hypothesised that FetA through toll-like receptor 4 (TLR4) and ROS production induces vascular dysfunction. Mesenteric arteries and vascular cells from WKY rats were studied. Vascular function was analysed by wire myography in the presence or absence of FetA (50 ng/mL) and/or CLI095 (CLI – 10–6M – TLR4 inhibitor). WKY vessels exposed to FetA were less sensitive to acetylcholine (Ach)-induced and sodium nitroprusside (SNP)-induced relaxation, while sensitivity to phenylephrine was increased by FetA; an effect blocked by N-acetylcysteine (antioxidant) and ML171 (Nox1 inhibitor). Inhibition of TLR4 blocked FetA effects on endothelial-dependent relaxation and contraction, but not on endothelial-independent relaxation. FetA increased ROS production (1 fold), but decreased H2 O2 intracellular levels (0.5 fold) in endothelial cells (EC) (p < 0.05); an effect blocked by CLI095. ROS production (0.5 fold), as well as, H2 O2 (0.5 fold) and ONOO- (1 fold) levels, were increased by FetA in VSMCs (p < 0.05). Protein oxidation was increased by FetA in VSMCs (1 fold, p < 0.05). In EC, eNOS inactivation (1 fold) and JNK activation (0.5 fold) were increased by FetA (p < 0.05). In VSMCs, Rho kinase activity was increased (2 fold, p < 0.05) at 30 min; while myosin light chain (MLC) activation was only increased (0.5 fold) at 15 min. In summary, FetA influences vascular function through Nox1-ROS dependent mechanisms. FetA-induced endothelial dysfunction and contractile responses involve TLR4. Our findings identify a novel system whereby FetA differentially influences vascular function through Nox1-ROS and TLR4